Manajemen Dana ZIS melalui Program Pemberdayaan Dapoer Ibu LAZIS Jateng Al Ihsan Pekalongan - Hanif Ardiansyah; Mirza Maulana; Dimas Prasetya (STIKes Ibnu Sina Ajibarang, 2025)
Dapoer Ibu is a Program of LAZIS Jateng Al-Ihsan Pekalongan, located in Rejosari Village, Bojong, Pekalongan. Contains of housewives who manage and develop catering businesses. This business is empowered by Lazis Jateng Al Ihsan to improve the economic of living of mustahiq so that they are free from poverty. This study aims to determine the strategy for managing ZIS funds for the Dapoer Ibu Lazis Jateng Al-Ihsan Program and how to improve the welfare of mustahik through the Dapoer Ibu community program. This study uses descriptive qualitative research. Data collection techniques through observation, interviews, and documentation. The results of this study show that Lazis Jateng Al-Ihsan Pekalongan in managing ZIS funds for the empowerment of the Dapoer Ibu community, it has implemented the POAC management function in the field. The stages of implementing the management function include planning, organizing, actuating, and controlling. In improving the welfare of mustahiq Lazis Jateng Al-Ihsan applies the concept of community empowerment in the form of: participation, access to information, capacity building, justice and equality, independence, and sustainability. By implementing this concept, the implementation of the program can be easier, and they can feel the results of this program sustainably.